Application of soymilk skin as sausage wrapping for improving lipid oxidation. Issue 6 (9th September 2020) - Lee, Jaesang; Kim, Yookyung
Abstract: Yuba, the soymilk skin, was developed as edible films for sausage. Yuba (Y) were prepared with added pine‐needle extract (YP) and employed to wrap sausage. Physical and mechanical properties and lipid oxidation of sausages were compared to sausages made with commercial collagen casing (C). Y films showed better transparency, oxygen‐barrier properties, and UV‐light barrier properties than C films ( p < .05). Particularly, the addition of pine‐needle extract increased DPPH activities from 31 to 48% and total phenol content from 7.52 to 14.64 mg gallic acid/g. Regarding application for sausage wrapping, Y (2.35%) and YP (2.66%) wrapped sausages with better protection against water loss during cooking compared to sausages made from C (5.84%). Especially, YP (3.57 MDA mg/kg) showed better protection against lipid oxidation for sausages than Y (4 MDA mg/kg) and C (4.62 MDA mg/kg) on day 6 after refrigerated storage. Yuba films could be employed as potential alternatives to gelatin films for manufacturing sausages.